MODERN THREATS AND DEFENSE STRATEGIES (American Journal of Interdisciplinary Research and Development, 2025)
In today’s interconnected world, the threat landscape is constantly evolving, driven by technological advancements, global interdependence, and increasingly sophisticated malicious actors. These modern threats span various domains, including cybersecurity, geopolitics, economic warfare, and climate change, with significant implications for national security, individual privacy, and corporate stability. This paper explores the nature of modern threats, particularly focusing on cyber threats, terrorism, geopolitical risks, and environmental challenges. Additionally, it examines contemporary defense strategies that governments, organizations, and individuals employ to mitigate these risks. From advanced cybersecurity systems to international collaboration frameworks and climate change mitigation, defense strategies have become more dynamic and multi-faceted. The paper aims to provide an in-depth analysis of the emerging threats of the modern world and the strategies in place to address them, evaluating their effectiveness and suggesting improvements for future preparedness.